Occupational health issues experienced by UK embryologists: informing improvements in clinical reproductive science practice. (8th August 2022) - Priddle, Helen; Pickup, Sarah; Hayes, Catherine; ,
Abstract: A consultation exercise was undertaken with UK embryologists to construct knowledge of the occupational health issues they experience in everyday practice. Data were obtained from 223 eligible survey responses. Work-related ill health was self-reported by 58.3% of respondents, 76.2% of whom reported multiple issues. The most frequently disclosed ill-health conditions were musculoskeletal disorders (45.3%) and stress and mental health problems (27.8%). Other issues with an incidence above 3% were ocular and auditory problems and needlestick and liquid nitrogen injuries. Shoulder injury or pain correspondingly increased in incidence with length of time in service. Absence from work and/or light duties were necessitated for 34.5% of those affected. Assessment of the evidence base for these work-related ill-health conditions explored contributory and ameliorating factors, which enabled a series of evidence-based recommendations to be formulated via the adoption of a GRADE-based framework.